The omnistat: A flexible continuous‐culture system for prolonged experimental evolution. Issue 8 (5th July 2020) - Ekkers, David M.; Branco dos Santos, Filipe; Mallon, Cyrus A.; Bruggeman, Frank; van Doorn, G. Sander
Abstract: Microbial evolution experiments provide a powerful tool to unravel the molecular basis of adaptive evolution but their outcomes can be difficult to interpret, unless the selective forces that are applied during the experiment are carefully controlled. In this respect, experimental evolution in continuous cultures provides advantages over commonly used sequential batch‐culture protocols because continuous cultures allow for more accurate control over the induced selective environment. However, commercial continuous‐culture systems are large and expensive, while available DIY continuous‐culture systems are not versatile enough to allow for multiple sensors and rigorous stirring. We present a modular continuous‐culture system that adopts the commonly used GL45 glass laboratory bottle as a bioreactor vessel. Our design offers three advantages: first, it is equipped with a large head plate, fitting two sensors and seven input/output ports, enabling the customization of the system for many running modes (chemostat, auxostat, etc.). Second, the bioreactor is small (25–250 ml), which makes it feasible to run many replicates in parallel. Third, bioreactor modules can be coupled by uni‐ or bi‐directional flows to induce spatiotemporal variation in selection. These features result in a particularly flexible culturing platform that facilitates the investigation of a broad range of evolutionary and ecological questions. To illustrate the versatility of our culturing system, we outline two evolution experiments that impose a temporally or spatially variable regime of selection. The first experiment illustrates how controlled temporal variation in resource availability can be utilized to select for anticipatory switching. The second experiment illustrates a spatially structured morbidostat setup that is designed to probe epistatic interactions between adaptive mutations. Furthermore, we demonstrate how sensor data can be used to stabilize selection pressures or track evolutionary adaptation. Evolution experiments in which populations are exposed to controlled spatiotemporal variation, are essential to gain insight into the process of adaptation and the mechanisms that constrain evolution. Continuous‐culture systems, like the one presented here, offer control over key environmental parameters and establish a well‐defined regime of selection. As such, they create the opportunity to expose evolutionary constraints in the form of phenotypic trade‐offs, contributing to a mechanistic understanding of adaptive evolution.